Abrasive waterjet cutting of boron carbide particles reinforced Al 6063 MMCs – A semi empirical modeling approach in the prediction of kerf angle. (August 2021) - Mohankumar, V.; Kanthababu, M.; Velayudham, A.
Graphical abstract: Highlights: Fabrication of unreinforced and reinforced Al6063 MMCs through stir casting. Experimental investigations on the effects of AWJC process variables on kerf angle. Prediction of kerf angle using Buckingham's π theorem for AWJC. Comparison between regression and semi empirical models. Identified best parameters combinations to achieve least kerf angle in AWJC of MMCs. Abstract: Currently, the use of abrasive waterjet cutting (AWJC) in the unconventional machining of hard particles reinforced light alloys, which is increasing in the aerospace machining industries, due to its inherent versatile machining characteristics. However, achieving higher dimensional accuracy is a challenge in the AWJC. This paper proposes a semi empirical factor-label method (dimensional analysis) to predict the resulting kerf angle during AWJC of unreinforced aluminum 6063 (Al 6063) and aluminum based metal matrix composites (MMCs) having varied percentage of boron carbide (B4 C) in Al 6063 namely 5%, 10% and 15%. Experiments were conducted using Box Behnken method considering four independent machining parameters viz. size of mesh ( ms ), mass flow rate of abrasives ( ma ), pressure ( p ) and feed rate ( u ) with each parameter at three levels and considering kerf angle as response parameter. Among the twenty-nine experimental trials, the # 80 size of mesh, 340 g/min of mass flow rate of abrasives, 200 MPa of pressure and 60 mm/min to 90 mm/min of feed rate combinations ensured with the least kerf angle. The experimental results were also modeled through regression equations for each material. Both the regression and dimensional analysis models were related to the data obtained through experimentation. The kerf angle modeled through dimensional analysis based semi empirical model has closer prediction with data obtained through experimentation.